2019
DOI: 10.1017/s1463423619000434
|View full text |Cite
|
Sign up to set email alerts
|

Are people’s health care needs better met when primary care is strong? A synthesis of the results of the QUALICOPC study in 34 countries

Abstract: Aim: This article synthesises the results of a large international study on primary care (PC), the QUALICOPC study. Background: Since the Alma Ata Declaration, strengthening PC has been high on the policy agenda. PC is associated with positive health outcomes, but it is unclear how care processes and structures relate to patient experiences. Methods: Survey data were collected during 2011–2013 from approximately 7000 PC physicians and 70 000 patients in 34, mainly Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 30 publications
0
28
0
3
Order By: Relevance
“…While smaller patient population size was clearly associated with better patient experience, only 2% to 18% of facility-level variation could be explained by measured covariates, suggesting further research is necessary in Mexico to identify levers for improvement. In the QUALICOPC study, conducted in 34—mainly European—countries, physicians providing a broader range of services and being paid through capitation had patients that reported more positive experiences, and more robust national primary care structure and higher health spending were also factors associated with better experience 16. In-depth exploration of high-performing facilities in Mexico would help provide insights into these and other characteristics of facilities and the broader health system that may influence patient experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While smaller patient population size was clearly associated with better patient experience, only 2% to 18% of facility-level variation could be explained by measured covariates, suggesting further research is necessary in Mexico to identify levers for improvement. In the QUALICOPC study, conducted in 34—mainly European—countries, physicians providing a broader range of services and being paid through capitation had patients that reported more positive experiences, and more robust national primary care structure and higher health spending were also factors associated with better experience 16. In-depth exploration of high-performing facilities in Mexico would help provide insights into these and other characteristics of facilities and the broader health system that may influence patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…At the health services level, variables such as presence of specific types of providers (eg, nurses, in addition to physicians), health facility structure (eg, fewer number of patients per provider, fewer numbers of physicians per practice, comprehensiveness of services provided by physicians) and functioning (eg, long weekly working hours, non-training vs training facilities, payment structure and operational agreements with other health systems) have been found to be associated with positive user experience with primary care 13–16…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on primary care demonstrates that each element of primary health care displays important roles and values. A study [ 7 ] conducted in 34 countries noted that more comprehensive, continuous, and accessible care in primary care was positively associated with patient experiences. In addition, better access to PCPs or having a regular physician with whom one has a personal relationship are related to fewer emergency department visits.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, several effects of primary care components for patient experiences and patterns of heath care utilization were noted. Such components and patient experience were also affected by medical structure; capitation payment was positively related with patient experience; people with lower incomes postponed more primary care visits for financial reasons [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study demonstrated the feasibility of obtaining favourable response rate in a survey involving doctors from public and private primary care settings Background A strong primary care system contributes to universal health coverage by providing affordable and equitable access to quality health services (Atun, 2004). To strengthen primary care, research on primary care is essential as it provides evidence for benchmarking and quality improvement initiatives (Schäfer et al, 2019). However, prior works have shown that primary care doctors are hard to engage in research (VanGeest et al, 2016), and primary care doctors' response rate has remained static despite increasing evidence on strategies to increase recruitment (Creavin et al, 2011).…”
mentioning
confidence: 99%